Pyloric giant Brunner's gland hamartoma as a cause of both duodenojejunal intussusception and obscure gastrointestinal bleeding - Kadim BAYAN; Yekta TÜZÜN; Şerif YILMAZ; Gülşen YILMAZ; Aslan BİLİCİ (Turkish Journal of Gastroenterology, 2019)
-